Tale(S) of twisted stomach: A case series of five patients - Syed Shafiq; Mallikarjun Patil; Harshad Devarbhavi (Medical Journal of Dr. D.Y. Patil Vidyapeeth, 2023)
Gastric volvulus (GV) is a clinical condition that occurs due to abnormal rotation of the stomach around its mesentery by at least 180° and can present as either acute, recurrent, intermittent, or chronic foregut obstruction. While acute GV is a surgical emergency, given the imminent risk of ischemic necrosis and perforation, patients with chronic GV present with nonspecific abdominal and chest symptoms, which may go unnoticed until diagnosed during endoscopic or radiologic evaluation. In this case series, we describe five patients with chronic GV; two of whom underwent endoscopy for chronic iron deficiency anemia, while two others presented with recurrent hiccups and one presented with chronic burning epigastric and retrosternal discomfort. Fortunately, in one of our patients, endoscopic devolvulation was successful without further recurrence of GV, while the other four patients are being managed conservatively and have remained relatively stable and without any complications on follow-up.